(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
One of the most significant political phenomenon in South America is the showing up of the so called progresist governments in countries such as Ecuador, Bolivia and Venezuela. This governments, that have been in functions for more than 15 years, as a foundational characteristic the destruction of the political representation in their respective countries and the creation of a social movements wave that got to be political and electoral fronts that allowed this parties to win. In this article we pay attention to two aspects related with changes in political culture and of citizenship conformation that are products of the progresism. These are the implementation of direct democracy mechanisms as a complement of liberal democracy and the presence of new processes of pluriethnic and plurinational integration. That is what has made progresist governments the supporters of democratic processes that are new and have helped de democratic transition since 1980 and 1990.